CT-Guided Chemical Thoracic Sympathectomy versus Botulinum Toxin Type A Injection for Palmar Hyperhidrosis - Yang, HongJun; Kang, Jianjie; Zhang, Shufen; Peng, Kairun; Deng, Bingmei; Cheng, Biao (The Thoracic and Cardiovascular Surgeon, 2019)
Background The present study aimed to evaluate and compare the efficacy of botulinum toxin type A (BTX-A) injection versus thoracic sympathectomy for idiopathic palmar hyperhidrosis.Methods Fifty-one patients with idiopathic palmar hyperhidrosis were treated with either BTX-A injection or thoracic sympathectomy between March 2013 and April 2016. The severity of palmar hyperhidrosis was qualitatively measured via the Hyperhidrosis Disease Severity Scale (HDSS). All patients completed a questionnaire that detailed the time taken for the treatment to work, local or systemic adverse effects, and pre- and post-treatment severity of hyperhidrosis. The efficacy and adverse effects of the two treatments were compared and analyzed.Results Hyperhidrosis-related quality of life improved quickly and significantly in the BTX-A group (26 patients) and the sympathectomy group (25 patients). Compared with pre-treatment, the HDSS score significantly reduced after treatment in both groups (p < 0.05). All patients in the sympathectomy group had cessation of sweating of the hands after treatment, and this curative effect lasted for 12 months. In contrast, the treatment took more time to work in the BTX-A group, and the curative effect lasted for a much shorter period (3 months). The sympathectomy group had a significantly lesser mean HDSS score than the BTX-A group at 1 week, 3 months, 6 months, 9 months, and 12 months after treatment (p < 0.05). The sympathectomy group experienced more complications than the BTX-A group.Conclusion For palmar hyperhidrosis, thoracic sympathectomy is more effective and has a longer lasting curative effect than BTX-A injection, but thoracic sympathectomy has more complications.
Keywords: palmar hyperhidrosis; botulinum toxin type A (BTX-A) injection; thoracic sympathectomy